Emergency Mobilities. (1st January 2016) - Adey, Peter
Abstract: This paper explores the relationship between mobilities and emergencies, two concepts that have shared little of the same space in research and critical debate. Emergency is a relatively taken-for-granted part of the political administration of events, life and the production and governance of mobility. Equally, mobilities and immobilities occur in, because of, or through emergency. Some mobilities could certainly be understood as emergency because whether in flight or response, emergencies demand highly intensive forms of movement that radically transform one's life chances and quality of life. The paper suggests that particular sets of mobilities occur and are compelled under certain kinds of conditions and forms of governance wielded under emergency politics, its legislation and practices. The paper works to identify several related characteristics of emergency mobility that have begun to be explored within existing literatures, burgeoning areas of enquiry and more conceptual writings, before concluding with a discussion of the implications of these themes for a more modest and provisional understanding of mobilities, emergencies and their governance.